2022
DOI: 10.3390/su142315538
|View full text |Cite
|
Sign up to set email alerts
|

Joint Estimation Method with Multi-Innovation Unscented Kalman Filter Based on Fractional-Order Model for State of Charge and State of Health Estimation

Abstract: This study simulates the polarization effect during the process of battery charging and discharging, and investigates the characteristics of the process. A fractional-order model (FOM) is established and the parameters of the FOM are identified with the adaptive genetic algorithm. As Kalman filter estimation causes error accumulation over time, using the fractional-order multi-innovation unscented Kalman filter (FOMIUKF) is a better choice for state of charge (SOC) estimation. A comparative study shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…where γ(k) is a monotonic increasing function of p(k), and its values range from 1 to 4, i.e., γ(k) ∈ [1,4]. Thus, it is concluded that γ(k) is a non-decreasing, bounded, and positive tuning factor.…”
Section: Lemma 1 ([38]mentioning
confidence: 89%
See 1 more Smart Citation
“…where γ(k) is a monotonic increasing function of p(k), and its values range from 1 to 4, i.e., γ(k) ∈ [1,4]. Thus, it is concluded that γ(k) is a non-decreasing, bounded, and positive tuning factor.…”
Section: Lemma 1 ([38]mentioning
confidence: 89%
“…In past years, a substantial amount of research has been devoted to advancing the field of adaptive control for continuous-time nonlinear systems. Numerous industrial processes exhibit nonlinear behavior, and various methods have been developed for identifying nonlinear systems, which can be applied to input nonlinear systems, output nonlinear systems, and systems with both input and output nonlinearities [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of estimating the SOC of EV battery pack, there are typically four common methods [12,13], which include ampere-hour (Ah) integral methods [14], OCV lookup SOC table methods [15], filter algorithms combined with equivalent circuit models [16], and data-driven algorithms [3]. The ampere-hour (Ah) integral method is commonly used to estimate SOC by integrating current and time over different time intervals.…”
Section: Estimation Of State Of Charge (Soc)mentioning
confidence: 99%